The Effectiveness of E-Leadership in Total Quality Management in Education - Sutono; Nurhayati Aida; Azainil (Sinergi International Journal of Education, 2024)
E-Leadership or digital leadership has become a key factor in supporting the adoption of Total Quality Management (TQM) in academic settings. This article explores the role of digital leadership in enhancing educational quality through TQM implementation. The study uses a qualitative approach with case study methods to analyze how school principals and educational leaders leverage digital technology to support TQM initiatives. The results indicate that digital leadership can enhance management effectiveness, increase student engagement, and improve learning outcomes. However, there are challenges in its implementation, including resource limitations and resistance to change. This research provides practical recommendations to overcome these challenges, including providing adequate training and support for teachers and staff, and fostering an organizational culture that supports innovation. Policymakers and educational leaders should find great value in these findings as they apply TQM and digital leadership to enhance the quality of education.